Effects of learning and teaching dimensions on experiences during DLSU’s online learning modality: Opportunities for curriculum change - Bello, Joanna Marie S. (Animo Repository, 2023)
The emergence of the COVID-19 pandemic has brought significant changes in the academe. Primarily, the decision by higher education institutions to shift from traditional learning to the online learning modality in order to ensure the continuance of education. Accordingly, the shift in modalities has affected the five dimensions of learning and teaching between students and faculty in terms of course content, interaction, skills, performance evaluation, and educational facilities, as discussed by previous literature. The purpose of this study is to determine the effect of the five dimensions of learning and teaching on the experiences of accounting students and faculty at De La Salle University - Manila and present recommendations for changes in the curriculum based on the findings. This study is significant as it provides the perspective of the students and the faculty and provides comparisons between the two in the context of DLSU. The study utilized a mixed method and confirmatory approach and involved a laborious process of collecting data through a survey instrument including Likert scales for quantitative data and open-ended questions for qualitative data. These were analyzed through statistical inference and thematic analysis, respectively. The quantitative findings yielded that there were no significant effects of the five dimensions to the learning and experience of the students and that there were no significant relationships between the five dimensions and teaching experiences of the faculty. On the other hand, the thematic analysis revealed the sentiments of the stakeholders pertaining to areas of improvement in the five dimensions of learning and teaching, based on their experiences during the transition to an online learning environment. As a result, this implies the need to revisit the current curriculum, policies, and practices to determine their aptness to the needs of the stakeholders, their integration of relevant industry developments, and their alignment with international standards.